Day-of-Surgery Video Calls and Phone Calls Increase Patient Satisfaction with Outpatient Surgery Experience: A Randomized Controlled Trial of Postoperative Communication Modalities. (3rd February 2021) - Kingery, Matthew T.; Hoberman, Alexander; Baron, Samuel L.; Gonzalez-Lomas, Guillem; Jazrawi, Laith M.; Alaia, Michael J.; Strauss, Eric J.
Abstract : Background: With the increasing utilization of patient satisfaction as a metric for clinical care, there is growing interest in techniques that can be used to improve satisfaction in patients undergoing surgery. The purpose of this trial was to assess the impact of day-of-surgery video and phone calls on patient satisfaction. Methods: We enrolled 251 patients undergoing outpatient orthopaedic surgery with 3 participating surgeons. Surgeons were randomized to 1 of 3 patient communication modalities: no contact (standard of care), phone call, or video call. Several hours following discharge on the day of surgery, the surgeons contacted patients according to their assigned treatment group. At the initial postoperative office visit, satisfaction outcomes were assessed using the Consumer Assessment of Healthcare Providers and Systems Surgical Care (S-CAHPS) survey and an additional satisfaction questionnaire. Results: Fifty-nine (97%) of 61 patients in the no-contact group, 118 (99%) of 119 patients in the phone group, and 71 (100%) of 71 patients in the video group completed follow-up assessment. The S-CAHPS top-box response rate in both the video group (0.86 ± 0.14, p < 0.001) and the phone group (0.84 ± 0.17, p < 0.001) was greater than in the no-contact group (0.68 ± 0.26). When asked to rate satisfaction with overall care, a greater proportion of patients in the video group (85.9%) gave the top-box response compared with both the phone group (71.8%, p = 0.040) and the no-contact group (60.7%, p = 0.002). Among the patients in the video group, 62.0% indicated that they would prefer a video call in future encounters with their surgeon compared with 1.8% of patients in the no-contact group (p < 0.001) and 1.7% of patients in the phone group (p < 0.001). Conclusions: Phone and video calls following discharge are an effective way of enhancing patient satisfaction with the clinical care experience as measured by the S-CAHPS survey. In terms of satisfaction with overall care, video calls may be superior to phone calls. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.